Reach for the Summit - M-S3-A1

Algebra Level 3

Given a positive infinite sequence { a n } \{a_n\} , S n = k = 1 n a k S_n = \displaystyle \sum_{k=1}^{n} a_k .

If n N + \forall n \in \mathbb N^+ , the arithmetic mean of a n a_n and 2 2 is equal to the geometric mean of S n S_n and 2 2 , then find a 2020 a_{2020} .


Reach for the Summit problem set - Mathematics


The answer is 8078.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Note that a 1 = S 1 a_1=S_1 , and from the defining statement:

a 1 + 2 2 = 2 S 1 = 2 a 1 , \frac{a_1+2}{2}=\sqrt{2S_1}=\sqrt{2a_1},

So then

a 1 + 2 = 8 a 1 ( a 1 + 2 ) 2 = 8 a 1 a 1 2 4 a 1 + 4 = 0 ( a 1 2 ) 2 = 0 a 1 = 2 \begin{aligned}a_1+2=\sqrt{8a_1}\implies (a_1+2)^2&=8a_1\\\iff a_1^2-4a_1+4&=0\\\iff (a_1-2)^2&=0\\\iff a_1&=2\end{aligned}

Continue like this to find a few terms, for example:

a 2 + 2 = 8 ( 2 + a 2 ) ( a 2 + 2 ) 2 = 8 ( a 2 + 2 ) a 2 = 2 or a 2 = 6 a 2 = 6 a n > 0 \begin{aligned}a_2+2=\sqrt{8(2+a_2)}\implies (a_2+2)^2&=8(a_2+2)\\\iff a_2&=-2 \textnormal{ or }a_2=6\\\iff a_2&=6\because a_n>0\end{aligned}

We obtain { a n } = { 2 , 6 , 10 , 14 , . . . } \{a_n\}=\{2, 6, 10, 14, ...\} , so guess that a n = 4 n 2 a_n=4n-2 .

Proof that a n = 4 n 2 a_n=4n-2 :

a n + 2 2 = 2 S n a n + 2 = 8 S n a n 2 + 4 a n + 4 = 8 S n S n = a n 2 + 4 a n + 4 8 ( ) \begin{aligned}\frac{a_n+2}{2}&=\sqrt{2S_{n}}\\\iff a_n+2&=\sqrt{8S_{n}}\\\implies a_n^2+4a_n+4&=8S_{n}\\\iff S_n&=\frac{a_n^2+4a_n+4}{8}\ (*)\end{aligned}

Fix a n = 4 n 2 a_n=4n-2 , so that

S n = r = 1 n 4 n 2 = 4 r = 1 n n 2 r = 1 n 1 = 4 ( n ( n + 1 ) 2 ) 2 n = 2 ( n 2 + n ) 2 n = 2 n 2 a n 2 + 4 a n + 4 8 = ( 4 n 2 ) 2 + 4 ( 4 n 2 ) + 4 8 = ( 16 n 2 16 n + 4 ) + ( 16 n 8 ) + 4 8 = 16 n 2 8 = 2 n 2 \begin{aligned}S_n&=\sum_{r=1}^n 4n-2\\&=4\sum_{r=1}^n n-2\sum_{r=1}^n 1\\&=4\left (\frac{n(n+1)}{2}\right )-2n\\&=2(n^2+n)-2n\\&=2n^2\\\\\frac{a_n^2+4a_n+4}{8}&=\frac{(4n-2)^2+4(4n-2)+4}{8}\\&=\frac{(16n^2-16n+4)+(16n-8)+4}{8}\\&=\frac{16n^2}{8}\\&=2n^2\end{aligned}

So a n = 4 n 2 a_n=4n-2 satisfies ( ) (*)\ \square .

a 2020 = 4 × 2020 2 = 8080 2 = 8078 \therefore a_{2020}=4\times 2020-2=8080-2=\color{#20A900}{\boxed{8078}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...